Evaluating Extension in Times of Crisis: Assessing Program Impact during COVID-19 - Catherine E. Dobbins; Kisha L. Faulk; Alexis Roberts; Alexa J. Lamm (Journal of International Agricultural and Extension Education, 2021)
Communicating the value of Extension programming to stakeholders remains a challenge for many Extension professionals. Program evaluation is a tool that can help communicate the value of Extension; however, many evaluation methods fail to articulate a story of aggregated impact. Apublic valueinstrument was recentlydeveloped to help communicate the impact ofExtension.Communicating Extension’s impact has become more critical, yet more difficult, to do during the COVID-19 pandemic. This research note shares the results of a program evaluation using the Extension public value instrument to determine the impact of GeorgiaCooperative Extension’s programs during the shelter-in-place orders due to COVID-19. Respondents (n= 572) indicated high levels of self-reported knowledge gain, wellness, intent to change behavior, and perceived economic value. The results demonstrated respondents’ overall satisfaction and valuation of Family and Consumer Sciences programs during COVID-19. The Extension public value instrument enabled evaluation data collectionfor Extension professionals to communicate the value of their program impact despite major disruptions to traditional program form
Keywords: evaluation; impact; crisis; COVID-19